A simulator of the MAJIS instrument onboard the JUICE mission: Description and application to operational and scientific cases - C. Royer; P. Haffoud; Y. Langevin; F. Poulet; D. Bockelée-Morvan; E. D’Aversa; M. Cisneros-González; D. Grassi; N. Ligier; G. Piccioni; J. Carter; F. Tosi; et al. (Planetary and Space Science, 2025)

Attenuation of Cellular Senescence and Improvement of Osteogenic Differentiation Capacity of Human Liver Stem Cells Using Specific Senomorphic and Senolytic Agents - Allancer D. C. Nunes; Louise E. Pitcher; Henry A. Exner; Diego J. Grassi; Brittan Burns; Maria Beatriz Herrera Sanchez; Ciro Tetta; Giovanni Camussi; Paul D. Robbins (Stem Cell Reviews and Reports, 2025)
Expansion of adult stem cells in culture increases the percent of senescent cells, reduces their differentiation capacity and limits their clinical use. Here, we investigated whether treatment with certain senotherapeutic drugs would reduce the accumulation of senescent cells during expansion of human liver stem cells (HLSCs) while maintaining their differentiation capacity. Our results demonstrate that chronic treatment with the senomorphic XJB-5-131 or the senolytics cocktail D + Q reduced the number of senescent cells and significantly reduced the expression of senescence-associated genes and several inflammatory SASP factors in later passage HLSCs. Additionally, treatment with XJB-5-131 and D + Q improved the capacity of HLSCs to undergo osteogenic differentiation following extensive in vitro expansion. Overall, our data demonstrate that treatment with XJB-5-13 or D + Q results in a reduction in the percentage of replication-induced senescent HLSCs and likely other types of adult stem cells and improve the potential therapeutic use of later passage human stem cells. Graphical abstract

Exploring the effects of decabromodiphenyl ether on meiofaunal communities: An experimental approach - E. Grassi; M. Greco; L. Guidi; M. Pasquariello; E. Al-Enezi; M. Trifuoggi; F. Frontalini; F. Semprucci (Marine Pollution Bulletin, 2025)

Cytogenetic analysis of meiotic behaviour and stability in a trigeneric hybrid (triticale x trigopiro) - M. Fradkin; E. J. Greizerstein; E. Grassi; V. Ferreira; M. R. Ferrari; L. Poggio (Protoplasma, 2024)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Novel application of FeIn2S4 as an efficient photo-Fenton catalyst for degradation of Ponceau 4R in aqueous solution - P. Grassi; J. da Silveira Salla; S. L. Jahn; E. L. Foletto (International Journal of Environmental Science and Technology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Lanostanoid triterpenes from the fungus Rigidoporus microporus - Yuliet A. Rincón; Gastón E. Siless; Lucía Daniela Amado; María Virginia Dansey; Emanuel Grassi; Nahuel Schenone; Gabriela M. Cabrera (Natural Product Research, 2021)

Effect of alcohol use disorder on cellular aging - Luana Martins de Carvalho; Corinde E. Wiers; Peter Manza; Hui Sun; Melanie Schwandt; Gene-Jack Wang; Rodrigo Grassi-Oliveira; Ana Lúcia Brunialti Godard; Nora D. Volkow (Psychopharmacology, 2019)

Association Between the Serum Uric Acid Levels and Lacunar Infarcts in the Elderly - F. Crosta; U. Occhiuzzi; G. Passalacqua; E. Occhiuzzi; A. Cimini; D. Grassi; C. Ferri; C. Marini; C. Borghi; G. Desideri (Journal of Molecular Neuroscience, 2018)

Interannual Variation in Diet, Dietary Diversity, and Dietary Overlap in Three Sympatric Strepsirrhine Species in Southeastern Madagascar - E. M. Erhart; S. R. Tecot; C. Grassi (International Journal of Primatology, 2018)

Acute inhibition of estradiol synthesis impacts vestibulo-ocular reflex adaptation and cerebellar long-term potentiation in male rats - Cristina V. Dieni; Aldo Ferraresi; Jacqueline A. Sullivan; Sivarosa Grassi; Vito E. Pettorossi; Roberto Panichi (Brain Structure and Function, 2018)

Gokyo Khumbu/Ama Dablam Trek 2012: effects of physical training and high-altitude exposure on oxidative metabolism, muscle composition, and metabolic cost of walking in women - E. Tam; P. Bruseghini; E. Calabria; L. Dal Sacco; C. Doria; B. Grassi; T. Pietrangelo; S. Pogliaghi; C. Reggiani; D. Salvadego; F. Schena; L. Toniolo; et al. (European Journal of Applied Physiology, 2016)

Fusarium spp. is able to grow and invade healthy human nails as a single source of nutrients - J. Galletti; M. Negri; F. L. Grassi; É. S. Kioshima-Cotica; T. I. E. Svidzinski (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Early abstinence of crack-cocaine is effective to attenuate oxidative stress and to improve antioxidant defences - Aline Zaparte; Thiago W. Viola; Rodrigo Grassi-Oliveira; Maurilio da Silva Morrone; José C. Moreira; Moisés E. Bauer (Psychopharmacology, 2015)

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)
Overviewing the European carbon (C), greenhouse gas (GHG), and non‐GHG fluxes, gross primary productivity (GPP) is about 9.3 Pg yr −1 , and fossil fuel imports are 1.6 Pg yr −1 . GPP is about 1.25% of solar radiation, containing about 360 × 10 18 J energy – five times the energy content of annual fossil fuel use. Net primary production (NPP) is 50%, terrestrial net biome productivity, NBP, 3%, and the net GHG balance, NGB, 0.3% of GPP. Human harvest uses 20% of NPP or 10% of GPP, or alternatively 1‰ of solar radiation after accounting for the inherent cost of agriculture and forestry, for production of pesticides and fertilizer, the return of organic fertilizer, and for the C equivalent cost of GHG emissions. C equivalents are defined on a global warming potential with a 100‐year time horizon. The equivalent of about 2.4% of the mineral fertilizer input is emitted as N 2 O. Agricultural emissions to the atmosphere are about 40% of total methane, 60% of total NO‐N, 70% of total N 2 O‐N, and 95% of total NH 3 ‐N emissions of Europe. European soils are a net C sink (114 Tg yr −1 ), but considering the emissions of GHGs, soils are a source of about 26 Tg CO 2 C‐equivalent yr −1 . Forest, grassland and sediment C sinks are offset by GHG emissions from croplands, peatlands and inland waters. Non‐GHGs (NH 3 , NO x ) interact significantly with the GHG and the C cycle through ammonium nitrate aerosols and dry deposition. Wet deposition of nitrogen (N) supports about 50% of forest timber growth. Land use change is regionally important. The absolute flux values total about 50 Tg C yr −1 . Nevertheless, for the European trace‐gas balance, land‐use intensity is more important than land‐use change. This study shows that emissions of GHGs and non‐GHGs significantly distort the C cycle and eliminate apparent C sinks.

Ex-situ conservation of Black poplar in Europe: genetic diversity in nine gene bank collections and their value for nature development - V. Storme; A. Vanden Broeck; B. Ivens; D. Halfmaerten; J. Van Slycken; S. Castiglione; F. Grassi; T. Fossati; J. E. Cottrell; H. E. Tabbener; F. Lefèvre; C. Saintagne; et al. (Theoretical and Applied Genetics, 2004)

Special Contribution: An Overview of Recent Seismic Refraction Experiments in Central Europe - A. Guterch; M. Grad; A. Špičák; E. Brückl; E. Hegedüs; G.R. Keller; H. Thybo; K. Aric; S. Acevedo; I. Asudeh; M. Behm; A. A. Belinsky; et al. (Studia Geophysica et Geodaetica, 2003)